Examples
Example 2
Example 3 Important
Example 4 Important Deleted for CBSE Board 2022 Exams
Example 5 Deleted for CBSE Board 2022 Exams
Example 6 Important
Example 7
Example 8 Important
Example 9 Important
Example 10
Example 11 (i)
Example 11 (ii) Important
Example 11 (iii) Important
Example 12
Example 13
Example 14 Important
Example 15 Important
Example 16 Deleted for CBSE Board 2022 Exams
Example 17 Important Deleted for CBSE Board 2022 Exams
Example 18
Example 19
Example 20 Important You are here
Example 21 Important
Example 22 Important
Examples
Last updated at Jan. 28, 2020 by Teachoo
Example 20 Let f = {(1, 1), (2, 3), (0, –1), (–1, –3)} be a linear function from Z into Z. Find f(x). Since f is a linear function, Let f(x) = mx + c. Putting value of x and y in the function For (1, 1) y = mx + c 1 = m(1) + c 1 = m + c m + c = 1 For (2, 3) y = mx + c 3 = m(2) + c 3 = 2m + c 2m + c = 3 Calculating (2) – (1) 2m + c – (m + c) = 3 – 1 2m + c – m – c = 2 2m – m + c – c = 2 m = 2. Putting m = 2 in (1) m + c = 1 2 + c = 1 c = 1 – 2 c = –1 So, f(x) = mx + c = 2x – 1